The Influence of the Ice Breaking Technique on Students' Learning Motivation in Science Subjects Class V B SD Negeri 94 Pekanbaru - Fajri, Auni; Rahmi, Laili (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to determine the effect of the Ice Breaking technique on the learning motivation of class V B students at SD Negeri 94 Pekanbaru. This research uses a type of quantitative research with a pre-experimental design, which is one of the research techniques that can be used to determine the impact of exclusive treatment on other people in a regulated environment, namely experimental research. This research was carried out at SD Negeri 94 Pekanbaru. This research was carried out on class V B students, totaling 32 students. The results of the research show a relationship between the application of ice breaking and student learning motivation, namely Ha is accepted and H0 is rejected, with the ice breaking variable (X) and the learning motivation variable (Y) having a significance value of 0.001 with a value of 0.05.